2015
DOI: 10.15850/amj.v2n4.640
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Mass Index with Menstrual Cycle in Senior High School Students

Abstract: Background: In recent years, there is an escalation of menstrual disorders in both developing and developed countries. One of the important factors that contribute to menstrual disorders is body fat content. In developing countries like Indonesia, young women in certain cultures get married at average age of 16 years. At the same time, the number of malnourishment among adolescent is increasing. This study was conducted to analyze the relationship between body mass index (BMI) and menstrual cycle in senior hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Moreover, an Indonesian study revealed that no relationship between body mass index (BMI) and menstrual interval and amount [38]. This may be due to there were no enough overweight (8.4%) or obese (1%) students in this study as compared to others.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, an Indonesian study revealed that no relationship between body mass index (BMI) and menstrual interval and amount [38]. This may be due to there were no enough overweight (8.4%) or obese (1%) students in this study as compared to others.…”
Section: Discussionmentioning
confidence: 64%
“…The Deshpande et al (2013) study was conducted with the aim of assessing body mass index and body fat with menstrual cycle pattern in adult girls, which showed the relationship between irregular menstrual cycles and high BMI (34). In a study by Ganesh et al (2013), which was conducted with the aim of linking body mass index and menstrual cycle pattern in high school girls, it was shown that there was no significant correlation between BMI and bleeding patterns (35). In addition, a study by Lee et al (2006), which was conducted with the aim of the menstrual cycle of teenage girls in Malaysia, showed that there was no significant relationship between BMI and menstrual cycle disorders such as duration of bleeding, bleeding volume, and irregular menstruation cycle (36).…”
Section: Discussionmentioning
confidence: 99%
“…The following tools were used in this study to collect data; a demographic proforma was used to collect demographic variables, a self-reported menstrual pattern questionnaire was used to identify the menstrual pattern among students that questionnaire with 12 items was developed by the investigator. 2 7 8 9 It includes menstrual characteristics and menstrual problems. The details of the menstrual cycle, including cycle length, number of days the period lasts, menstrual flow, dysmenorrhea, menorrhagia, polymenorrhagia, oligomenorrhea, hypomenorrhea, and amenorrhea, are measured by a self-reported menstrual pattern questionnaire.…”
Section: Methodsmentioning
confidence: 99%